Open‐Cage Fullerene as Molecular Container for F−, Cl−, Br− and I−. (27th November 2022) - Sun, Shijun; Liu, Zhen; Colombo, Francesca; Gao, Rui; Yu, Yuming; Qiu, Yi; Su, Jie; Gan, Liangbing
Abstract: A 19‐membered open‐cage fullerene derivative was prepared from C60 in 7 steps and 5.5 % yield through the peroxide‐mediate pathway. There are four carbonyl groups, an ether oxygen and a quinoxaline moiety on the rim of the orifice. A chloride anion could be inserted into its cavity by heating with hydrochloric acid at 60 °C for 4 h. Encapsulation of fluoride, bromide and iodide anions was also achieved at slightly more forcing conditions, 90 °C for 14 h. Single crystal X‐ray structures of the sodium salt of the chloride and the bromide encapsulated derivatives were obtained, which showed the halide anion in the center of the cavity and two sodium cations connecting two cages through coordination to the oxygen atoms on the rim of the orifices. The halide encapsulation ratio is quantitative in the isolated products. Abstract : Halide anions have been successfully inserted into the cavity of a 19‐membered open‐cage fullerene derivative at 60 °C for Cl − and 90 °C for F −, Br − and I − under atmospheric pressure. The encapsulation ratio is quantitative as shown by single crystal X‐ray diffraction analysis data and spectroscopic data. The presence of halide ions improves the stability of the cage structure, which could be stored at r.t. for weeks without noticeable change.